Ответы 2

  • Ответ:

    Пошаговое объяснение:

    (х+2)²-(х-2)²=х²+4х+4-(х²-4х+4)= х²+4х+4-х²+4х-4=8х

    • Автор:

      halfling
    • 5 лет назад
    • 0
  • Пошаговое объяснение:

    (x+2)² - (x-2)² = 8x

    (x+2)² - (x-2)² = x² + 2*x*2 + 2² -x² + 2*x*2 - 2² = x² + 4x + 4 - x² +4x - 4 = 8x

    • Автор:

      stout
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years